Combinatorial Therapeutic Strategies and Multi-Modal Synergies for Functional HIV Remission: Modeling and Optimization of Integrated Therapeutic Sequences - Barack Ndenga (Publisher, 2026)
The persistence of HIV-1 despite effective antiretroviral therapy (ART) reveals a fundamental truth: single-modality interventions are architecturally insufficient for achieving durable remission or cure. HIV latency, immune dysfunction, and viral rebound are governed by interconnected biological systems that cannot be dismantled in isolation. In this article, I examine combinatorial therapeutic strategies that integrate pharmacological, immunological, genetic, and computational modalities to achieve functional HIV remission. I place emphasis on the rational design, temporal sequencing, and systems-level optimization of multi-modal interventions. I argue that the future of HIV cure research lies not in awaiting a singular breakthrough, but in the precision orchestration of therapeutic ecosystems. Keywords: HIV cure,Functional remission,Combinatorial therapy,Therapeutic synergy,Multi-modal intervention,Temporal sequencing,Systems optimization,Computational modeling,Shock and Kill,Treatment interruption,Latency reversing agents (LRAs),CAR-T cells,Broadly neutralizing antibodies (bNAbs),Therapeutic vaccine,Precision medicine
The persistence of HIV-1 despite effective antiretroviral therapy (ART) reveals a fundamental biological truth: single-modality interventions are architecturally insufficient for achieving a durable cure or remission. HIV latency, immune dysfunction, and viral rebound are governed by interconnected systems that cannot be dismantled in isolation. In this article, I examine the paradigm of combinatorial therapeutic strategies that integrate pharmacological, immunological, genetic, and computational modalities. I emphasize the rational design, critical temporal sequencing, and systems-level optimization required to transform isolated interventions into coherent, synergistic therapeutic ecosystems. This work argues that the future of HIV cure research lies not in a singular 'magic bullet,' but in the precision orchestration of multi-modal approaches to achieve realistic, functional remission.